2019
DOI: 10.1186/s13046-019-1084-4
|View full text |Cite
|
Sign up to set email alerts
|

Poly-specific neoantigen-targeted cancer vaccines delay patient derived tumor growth

Abstract: Background Personalized cancer vaccines based on neoantigens have reached the clinical trial stage in melanoma. Different vaccination protocols showed efficacy in preclinical models without a clear indication of the quality and the number of neoantigens required for an effective cancer vaccine. Methods In an effort to develop potent and efficacious neoantigen-based vaccines, we have developed different neoantigen minigene (NAM) vaccine vectors to determine the rules for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…It is still not clear whether one antigen is superior to another in terms of frequency of immune response or clinical effect [133]. In one study, it has been shown that neoantigens with a predicted high affinity are more immunogenic and that a poly-specific and poly-functional DNA vaccine encoding neoantigens was the most efficient solution to prevent tumor growth in mice [134]. Further studies are needed to generalize these findings.…”
Section: Introductionmentioning
confidence: 99%
“…It is still not clear whether one antigen is superior to another in terms of frequency of immune response or clinical effect [133]. In one study, it has been shown that neoantigens with a predicted high affinity are more immunogenic and that a poly-specific and poly-functional DNA vaccine encoding neoantigens was the most efficient solution to prevent tumor growth in mice [134]. Further studies are needed to generalize these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been attempted to improve CTL responses such as nanomaterial-based as well as DNA-based vaccination. Nanomaterial vaccines promote antigen uptake and prolong the presentation time on APC (9, 10, 39), while DNA vaccines promote antigen processing and presentation (11, 40). Nevertheless, these strategies have not been successfully used for the weak neoantigens.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor neoantigens are attractive targets for cancer vaccine design (6). Both preclinical (711) and early phase clinical studies (1214) found that neoantigen-based poly-epitope vaccines can substantially expand the tumor-specific T cell pools, and steer the immune system to the selective destruction of cancers with limited off-target toxicities, which leads to cancer regression and long-term tumor-free survival.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, neoantigen-based vaccines are being studied as novel cancer immunotherapies because they can enhance the immune responses to tumor cells [77, 78]. Preclinical studies have shown that the neoantigen-based cancer vaccines are effective and feasible in mouse tumor models, including melanoma, colon cancer, and glioma [68, 7982]. For example, neopeptides containing IDH1 (R132H) p123-142 mutation region were synthesized and bound to transgenic human MHC-II molecules.…”
Section: Cancer Immunotherapy: Classification Clinical Status Advanmentioning
confidence: 99%